2012
DOI: 10.1111/j.1365-2443.2012.01583.x
|View full text |Cite
|
Sign up to set email alerts
|

DNA–RNA hybrid formation mediates RNAi‐directed heterochromatin formation

Abstract: Certain noncoding RNAs (ncRNAs) implicated in the regulation of chromatin structure associate with chromatin. During the formation of RNAi-directed heterochromatin in fission yeast, ncRNAs transcribed from heterochromatin are thought to recruit the RNAi machinery to chromatin for the formation of heterochromatin; however, the molecular details of this association are not clear. Here, using RNA immunoprecipitation assay, we showed that the heterochromatic ncRNA was associated with chromatin via the formation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
89
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(99 citation statements)
references
References 60 publications
6
89
2
2
Order By: Relevance
“…Consistent with a previous observation (Nakama et al 2012), we found low levels of DNA:RNA hybrids at subtelomeres in wild-type cells (Fig. 4F).…”
Section: Absence Of Rna Degradation Leads To Changes In Chromatin Orgsupporting
confidence: 81%
See 1 more Smart Citation
“…Consistent with a previous observation (Nakama et al 2012), we found low levels of DNA:RNA hybrids at subtelomeres in wild-type cells (Fig. 4F).…”
Section: Absence Of Rna Degradation Leads To Changes In Chromatin Orgsupporting
confidence: 81%
“…It has been shown that chromatin retention of RNA and DNA:RNA hybrid formation establish RNAi-mediated heterochromatin (Sun et al 2013;SkourtiStathaki et al 2014;Yu et al 2014). Deletion of RNase H, however, has a defect in heterochromatin maintenance, indicating that an excess of DNA:RNA hybrids has a negative impact on heterochromatin assembly (Nakama et al 2012). DNA:RNA hybrids were ′ tlh: second half) or LEU2 were inserted ∼5.5 kb upstream of tlh under the thiamine-inducible nmt1 promoter.…”
Section: Discussionmentioning
confidence: 99%
“…4А). Эти олигонуклеотиды должны формировать нековалентные комплексы c EGPO и блокировать его действие [17]. С помощью ОТ-ПЦР показали, что три олигонуклеотида блокировали АС, что подтвердило правильность гипотезы и позволило определить размер EGPO на уровне 47 нуклеотидов (рис.…”
Section: идентификация и экспрессия рнк-олигонуклеотида образующегосunclassified
“…The first is a siRNA/DNA-binding model [65,136] , during which the RITS complex binds directly to chromatin. This binding seems to be dependent on the interaction between the siRNA and its DNA-target sequence.…”
Section: Tgsmentioning
confidence: 99%